2019
DOI: 10.1039/c9cp03826d
|View full text |Cite
|
Sign up to set email alerts
|

CO2 reutilization for methane production via a catalytic process promoted by hydrides

Abstract: CO2 is recycled to produce CH4 selectively by using complex hydrides as the hydrogen source and catalytic metal particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 39 publications
1
41
0
Order By: Relevance
“…29,30 More recent studies showed that CO 2 can be reduced on the surface of hydrides that act as catalysts, by means of the Sabatier reaction allowing the conversion of CO 2 to methane and closing the cycle of carbon. [31][32][33][34][35][36][37] This allows the use of H 2 stored safely in a solid matrix (MHx, M: metal, H: hydrogen), which could acts as a catalyst for the transformation of CO 2 into a gaseous fuel. In particular, it was found that some complex hydrides such as, for example, Mg 2 NiH 4 , Mg(BH 4 ) 2 , and LiAlH 4 possess good catalytic properties for the hydrogenation of CO 2 , generating different chemical compounds of industrial interest.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…29,30 More recent studies showed that CO 2 can be reduced on the surface of hydrides that act as catalysts, by means of the Sabatier reaction allowing the conversion of CO 2 to methane and closing the cycle of carbon. [31][32][33][34][35][36][37] This allows the use of H 2 stored safely in a solid matrix (MHx, M: metal, H: hydrogen), which could acts as a catalyst for the transformation of CO 2 into a gaseous fuel. In particular, it was found that some complex hydrides such as, for example, Mg 2 NiH 4 , Mg(BH 4 ) 2 , and LiAlH 4 possess good catalytic properties for the hydrogenation of CO 2 , generating different chemical compounds of industrial interest.…”
mentioning
confidence: 99%
“…In particular, it was found that some complex hydrides such as, for example, Mg 2 NiH 4 , Mg(BH 4 ) 2 , and LiAlH 4 possess good catalytic properties for the hydrogenation of CO 2 , generating different chemical compounds of industrial interest. [31][32][33][34][35] Although the decomposition of alanates in atmospheres with CO 2 has been little explored, it is known that at temperatures greater than 120°C, LiAlH 4 reacts with CO 2 , producing CH 4 , H 2 and metal oxides.…”
mentioning
confidence: 99%
See 3 more Smart Citations